Single Institution Early Experience with the Bundled Payments for Care Improvement Initiative. (4th January 2017) - Iorio, Richard; Bosco, Joseph; Slover, James; Sayeed, Yousuf; Zuckerman, Joseph D.
Abstract : Abstract: The Centers for Medicare & Medicaid Services (CMS) implemented the Bundled Payments for Care Improvement (BPCI) initiative in 2011. Through BPCI, organizations enlisted into payment agreements that include both performance and financial accountability for episodes of care. To succeed, BPCI requires quality maintenance and care delivery at lower costs. This necessitates physicians and hospitals to merge interests. Orthopaedic surgeons must assume leadership roles in cost containment, surgical safety, and quality assurance to deliver cost-effective care. Because most orthopaedic surgeons practice independently and are not employed by hospitals, models of physician-hospital alignment (e.g., physician-hospital organizations) or contracted gainsharing arrangements between practices and hospitals may be necessary for successful bundled pricing. Under BPCI, hospitals, surgeons, or third parties share rewards but assume risks for the bundle. For patients, cost savings must be associated with maintenance or improvement in quality metrics. However, the definition of quality can vary, as can the rewards for processes and outcomes. Risk stratification for potential complications should be considered in bundled pricing agreements to prevent the exclusion of patients with substantial comorbidities and higher care costs (e.g., hip fractures treated with prostheses). Bundled pricing depends on economies of scale for success; smaller institutions must be cautious, as 1 costly patient could substantially impact the finances of its entire program. CMS recommends a minimum of 100 to 200 cases yearly. We also suggest that participants utilize technologies to maximize efficiency and provide the best possible environment for implementation of bundled payments. Substantial investment in infrastructure is required to develop programs to improve coordination of care, manage quality data, and distribute payments. Smaller institutions may have difficulty devoting resources to these infrastructural changes, although changes may be implemented more thoroughly once initiated. Herein, we discuss our early total joint arthroplasty BPCI experience at our tertiary-care academic medical center.